The Discussion on Mediation of Innovation Capital toward Human Capital and Performance : A Case Study of the Industry of Integrated Circuit Design - Lee, Yueh-Chiang; Yang, Yao-Hung; Huang, Wen-Tsung (Archives of Business Research, 2019)
There are many studies of intellectual capital affecting enterprise performance, but no empirical research has been carried out by scholars on mediation effect of innovation capital between human capital and enterprise performance. This research selects Taiwan’s listed and OTC companies in the industry of integrated circuit design are selected as a case study and with the Panel data model verifies their correlation. It is discovered from the research result that employee value added in human capital correlates positively with enterprise performance; employee productivity in human capital has positive correlation with R&D intensity in innovation capital; employee value added in human capital shows positive correlation with R&D productivity in innovation capital. Those verify and demonstrate innovation capital is the mediator between human capital and enterprise performance.